Review of experimental approaches for improving zT of thermoelectric materials - Ma, Zhe; Wei, Jiangtao; Song, Peishuai; Zhang, Mingliang; Yang, Liangliang; Ma, Jing; Liu, Wen; Yang, Fuhua; Wang, Xiaodong (Materials science in semiconductor processing, 2021)
In the past years, various work has been devoted to improving the thermoelectric figure of merit zT, and remarkable advances have been achieved. In 2019, an abnormal zT value exceeding 400 in the Cu2Se system was measured experimentally by a Japanese group. In 1993, the theoretically predicted maximum zT value for a 0.5-nm-wide Bi2Te3 quantum wire was just 14. Sometimes, large deviations exist between experimental results and theoretical predictions. It is necessary to summarize the recent experimental results associated with the improvement of zT. In principle, the improvement of zT value arises from a high power factor and a low thermal conductivity, whereas a high power factor stems from a high Seebeck coefficient and a high electrical conductivity. Herein, several approaches were reviewed, including increasing Seebeck coefficient, electrical conductivity, power factor, and decreasing thermal conductivity to improve thermoelectric performances. In every experimental study, the underlying mechanisms, such as material components, atomic structure characterizations, and fabrication processes for enhancement of thermoelectric performances were discussed in detail. All experimental-based references have major implications for researchers in related fields. Finally, the current challenges hindering the further improvement of zT value were pointed out, and several promising routes were proposed. [Display omitted] •The recent experimental advances on improving thermoelectric performances were reviewed.•The synthesis techniques, material components, atomic structures and device architectures were highlighted.•Several promising routes and applications of thermoelectric materials and devices were also proposed.